STUDY ON THE FRICITON AND WEAR BEHAVIORS OF MODIFIED HDPE/GLASS SPHERES COMPOSITES - (:unkn) unknown (SERBAN SOLACOLU FOUNDATION, 2015)
In the present work, high density polyethylene based composites filled with glass spheres (hollow) and HDPE/glass spheres (filled with alumina silicate) particles were prepared. Fillers contents In the HDPE were 5, 10, 15, and 20 wt%. The mechanical, morphological and tribological properties of the polymer composites were investigated. Substantial improvements In the some mechanical properties were obtained by the addition of filler. For example, the results showed that the elasticity modulus of composites improved with increasing the glass spheres content The addition of fillers to the HOPE changed significantly the friction coefficient and wear rate of the composites. HDPE filled with a high level content of fillers showed higher wear rate than pure HOPE under dry sliding. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM).
Keywords: Tribological behavior; Wear; Mechanical properties; Friction; Polystyrene; High density polyethylene; Glass sphere; MOLECULAR-WEIGHT POLYETHYLENE; MECHANICAL-PROPERTIES; TRIBOLOGICAL PROPERTIES; SURFACE MODIFICATION; FRICTION; NANOCOMPOSITES; CRYSTALLINITY